Accounting Standards for Semi-Autonomous Agencies: Experiences and Lessons from Indonesia - Waluyo, Budi (The Indonesian Journal of Accounting Research, 2021)
The adoption of accrual accounting in government agencies has been so widespread. Following the global trend, Indonesian administration has implemented governmental accounting standards for its agencies. This study aims to explain accounting standards in the context of agencification, i.e. the use of semi-autonomous agencies to deliver public services. The paper explores formulation and implementation of accounting standards by investigating case studies from semi-autonomous agencies in Indonesia. The data were collected through semi-structured interviews with agency officials, policymakers, standards-setters, and experts. The results were analyzed through an inductive-deductive approach. The study shows that whilst accrual accounting has stimulated fundamental change on financial reporting in the agencies, thus dual accounting standards at the beginning of the adoption is considered unnecessary by agency managers, policymakers, and standard-setter. The research also finds a constraint in the accounting system design that could hinder agencies to improve their financial reporting.